Industrial Technology Program Quality Assurance: A Preliminary Industry-Academe Skills Competency Study on Concurrent Engineering Demands - Cuasito Sr, Ruvel J.; Namoco, Consorcio S. (JPAIR Multidisciplinary Research, 2010)
This paper provides fundamental insights on industrial technology program quality assurance with regards to the latest trends in concurrent engineering and mechatronics in the manufacturing industries. It tackles on the curricular program analysis that attempts to examine existing program relevance to concurrent engineering needs and practices in Region X. The fundamental arguments are anchored on the issue of industry-academe imbalance relative to human resource quality. Issues presented in this paper points to some academic shortcomings and industry's lackluster academic involvement. This imbalance are confirmed and validated through the academic and industry assessment process which attempted to compare industry's actual skills competency needs and the quality of human resources supplied by the academe and or other training institutions. Appropriate complementary curricular program initiatives and industry collaboration were undertaken to address prevailing arguments. The study outcome is perceived to provide sustainable quality assurance in industrial technology program offerings of Mindanao University of Science and Technology in Cagayan de Oro City, Philippines.
Keywords: Quality Assurance; Mechatronics; Competency-based; Curriculum